ANALISIS STRATEGI PENGEMBANGAN BMT: STUDI KASUS PADA BMT DANA MENTARI, PURWOKERTO JAWA TENGAH - Amanda Rahma Januarizki; Sekar Dwi Kunanti; Farhan Muzaki (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to analyze the development of Baitul Maal wat Tamwil (BMT) using a SWOT approach to identify the strengths, weaknesses, opportunities, and threats in its operational activities. Using qualitative methods, data was collected through interviews, observations, and documentation studies on selected BMTs. The analysis results reveal that the main strength of BMT lies in its flexible Islamic services and strong relationships with the local community, while weaknesses include limited capital and technology. Development opportunities are driven by increasing public awareness of Islamic finance; however, threats such as competition from conventional financial institutions and strict regulations need to be anticipated. This research recommends strategies for strengthening management, utilizing digital technology, and enhancing Islamic financial literacy to support sustainable growth of BMT.